KCNQ and KCNE Isoform-Dependent Pharmacology Rationalizes Native American Dual Use of Specific Plants as Both Analgesics and Gastrointestinal Therapeutics - Abbott, Geoffrey W.; Redford, Kaitlyn E.; Yoshimura, Ryan F.; Manville, Rían W.; Moreira, Luiz; Tran, Kevin; Arena, Grey; Kookootsedes, Alexandra; Lasky, Emma; Gunnison, Elliot (Frontiers in Physiology, 2021)
Indigenous peoples of the Americas are proficient in botanical medicine. KCNQ family voltage-gated potassium (Kv) channels are sensitive to a variety of ligands, including plant metabolites. Here, we screened methanolic extracts prepared from 40 Californian coastal redwood forest plants for effects on Kv current and membrane potential in Xenopus oocytes heterologously expressing KCNQ2/3, which regulates excitability of neurons, including those that sense pain. Extracts from 9 of the 40 plant species increased KCNQ2/3 current at -60 mV by ≥3-fold (maximally, 15-fold by Urtica dioica) and/or hyperpolarized membrane potential by ≥-3 mV (maximally, -11 mV by Arctostaphylos glandulosa). All nine plants have traditionally been used as both analgesics and gastrointestinal therapeutics. Of two extracts tested, both acted as KCNQ-dependent analgesics in mice. KCNQ2/3 activation by tannic acid, gallic acid and quercetin provided molecular correlates for analgesic action of several of the plants. While tannic acid also activated KCNQ1 and KCNQ1-KCNE1, it inhibited KCNQ1-KCNE3, mechanistically rationalizing use of tannic acid-containing plants as gastrointestinal therapeutics. KCNE dependence of KCNQ channel modulation by plant metabolites therefore explains Native American use of specific plants as both analgesics and gastrointestinal aids.